Analisis Segmentasi, Targeting Dan Positioning Melalui Program Siaran Pada Radio Mitra Batu - Warter Agustim (BIP's JURNAL BISNIS PERSPEKTIF, 2015)
This research was caused by the changing environment and other supporting factors. The changing of business pattern of seller market to buyer market made a company has to adapt their need and changing behaviour. By having this base a company need to do market segmenting, targeting, and positioning with broadcast program in order to serve customers having different characteristics. This research aimed to find out how to apply segmenting, targeting dan positioning (STP) in Mitra 97.0 FM Radio of Batu City in determining the marketing strategy by considering STP. This research used also descriptive method drawing the execution of STP and the lack of the company in implementing STP. Form the analysis result done, Mitra 97.0 FM Radio of Batu City tried to serve the large market and divide its customers (listeners) in several segmenting variables. The applied marketing strategy was by developing products and promoting sales by personal selling, publishing, and advertising. In executing this strategy Mitra FM Radio of Batu hoped that it could be a radio having incisive segments and advertising media for products agree with the customers (listeners) segment concerned.